Geometrical integrity of micromold cavity sputtered by FIB using multilayer slicing approach - Ali, Mohammad Yeakub; Loo, Yee Wei (Springer Berlin / Heidelberg, 2007)
This paper discusses the investigation of geometrical integrity of micromold cavity produced by focused ion beam (FIB) sputtering slice by slice. Parabolic shaped micromold cavity was chosen as an example. Preliminary experiments were carried out to characterize the machine and select the optimum process parameters such as beam current, pixel spacing, aperture size, and dwell time. The geometrical integrity of the sputtered micromold cavity was analyzed based on three selected criteria such as aspect ratio, cross-sectional area, and area offset. The theoretical and sputtered profiles were compared. The investigation showed that the measured aspect ratio was almost equal to the theoretical aspect ratio for low aspect ratio microcavity. For high aspect ratio cavity, the measured aspect ratio was higher than the theoretical aspect ratio by 5–8%. The area offset was found to be 5–10% of the theoretical area. The variation in theoretical and sputtered cross-sectional area was 2–4%. The characterization showed that the geometrical integrity of micromold cavity sputtered by FIB using slicing approach was high.